Determination of Carbofuran on Hydrophilic Interaction Liquid Chromatography Using Tsk Gel Amide 80 As Stationary Phase - A. Kurnia; L.W. Lim; T. Takeuchi (Jurnal Keselamatan Radiasi dan Lingkungan, 2016)
The hydrophilic interaction liquid chromatography (HILIC) coupled to environmental friendly capillary liquid chromatography was employed to investigate retention behavior of carbofuran. Aim of this research is to investigate retention behavior of carbofuran using TSK gel amide 80 as stationary phase. Several condition was conducted to investigate retention behavior of carbofuran such as comparison study of TSK gel amide 80 with other polar column, comparison study retention behavior of carbofuran on various system wavelength, water content effect in HILIC mode, effect of buffer concentration on HILIC mode, and analytical performance. Results showed that TSK gel imidazole was superior compare to other polar stationary phase on determine carbofuran, wavelenght 251 and 254 nm was resulting higher absorbance for carbofuran than others, increase of water content on mobile phase was decrease the retention time, also increase buffer salt concentration was decrease the retention time and according to analysis performance that is the accuracy was 101±10,1, the LOD 0.66 ppm while LOQ 2.22 ppm. As conclusions that TSK gel amide 80 was offering good determine on carbofuran even using capillary liquid chromatography with 10 cm length of column.